How to address the question of Uighur persecution - Ahsan, Abdullahil (Turkey Agenda, 2015)
The Turkish daily Hurriyet has reported that, “World Uighur Congress (WUC) head Rebiya Kadeer has criticized Chinese oppression of the Uighur Turks living in China’s northwestern region of Xinjiang, saying that massacres, extrajudicial executions and oppression against Uighurs was continuing (July 8).” Earlier protesters in Turkey have demonstrated in support of Uighur minorities in against alleged Chinese persecution of the minority community. Some extremists have even attacked South Korean tourists by mistake thinking that they were Chinese tourists and some opposition politicians blatantly expressed their support for violent acts. In fact since the beginning of the holy month of Ramadan news about the persecution of Uighur Muslims in Southern China are making headlines in many parts of the Muslim world. If I remember correctly, we had witnessed the similar news during Ramadan last year as well.